(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2018)
How is our temporal experience possible? When we hear a song, we are aware that every note is before and after another note (and that’s how we remember it), but we also ’experience-as-present’ more than one note at a time. To answer this question, I suggest an analogy with the diﬀerence drawn, in the spatial case, between the two diﬀerent mechanisms of counting and ’subitizing’ (the immediate visual capture of a certain number of items as a single object). My proposal is to identify two diﬀerent mechanisms even in the temporal case: a temporal counting, a coconscious experiential ’single look’ of a temporal interval; and a temporal subitizing, an atomic storing operation which organizes every event in a mathematical, point-like sequence. These two mechanisms are taken to be operative always and together; we never cease to store the events encountered in a temporal line, but we also experience a subgroup of them as present.